An Innovative GIS-Based Policy Approach to Stream Water Quality and Ecological Risk Assessment in Mediterranean Regions: The Case of Crete, Greece - Nektarios N. Kourgialas; Chrysoula Ntislidou; Eleana Kazila; Agathos Filintas; Catherina Voreadou (Land)
Due to the multiple pressures from human activities, many freshwater ecosystems are facing degradation. To address this issue, a new approach for assessing stream water quality and ecological (WQE) risk using a multi-criteria analysis through a GIS-based policy tool has been developed. The suggested methodology integrates eight different factors along the contaminant pathway from source to streams, including: (a) rainfall variability, (b) soil texture, (c) soil erodibility, (d) slope, (e) river buffer zone, (f) point source contamination buffer zone, (g) non-point source contamination of NO3, and (h) non-point source contamination of PO4. Utilizing fuzzy GIS tools, the above factors and their related maps were spatially overlaid (raster-based suitability for raster reclassification) to obtain the final stream WQE risk map. The final map depicts the spatial distribution of streams concerning their water quality risk and is represented by two classes of WQE risk. The first class is characterized as “appropriate”, in which there is no need for any further actions, while the other one is characterized as “non-appropriate”, indicating that actions should be taken to ensure the sustainability of streams’ water quality. The proposed approach was implemented for the island of Crete, which is located in the Southeast Mediterranean region. The developed methodology was validated using the Hellenic evaluation system (HESY2), an especially established and adapted to the Mediterranean river systems ecological quality metric method, obtained by in situ measurements that were conducted during different monitoring programs (1989–2015). Moreover, this study summarizes appropriate measures and practices that ensure the sustainable management of Mediterranean river basins. These practices can be adopted by local authorities, owners of polluting units, and farmers/breeders to improve the resiliency of streams’ water quality issues in the Mediterranean region.